Treatment of urea manufacturing facility effluent by Hopea odorata and Khaya ivorensis - Yavari, S. (IWA Publishing, 2017)
Phytoremediation is an environmentally friendly and sustainable alternative for treatment of nitrogen-enriched wastewaters. In this study, Ta-khian (Hopea odorata) and Lagos mahogany (Khaya ivorensis), two tropical timber plants, were investigated for their performances in treatment of urea manufacturing factory effluent with high nitrogen (N) content. Plant seedlings received four concentrations of N (190, 240, 290 and 340 mg/L N) in laboratory-scale constructed wetlands every 4 days for a duration of 8 weeks. The solution volumes supplied to each container, amount of N recovered by plants and plant growth characteristics were measured throughout the experiment. Results showed that Ta-khian plants were highly effective at reducing N concentration and volume of water. A maximum of 63.05 N recovery was obtained by Ta-khian plants grown in 290 mg/L N, which was assimilated in the chlorophyll molecule structure and shoot biomass. Significant positive correlations have been shown between N recovery percentages and plant growth parameters. Ta-Khian plants can be applied as suitable phytoremediators for mitigating N pollution in water sources. © IWA Publishing 2017.